Machine learning for Precise Targeting of a Mobile Dialectical Behavior Therapy Skills Training Application - Czerwinski, Mary; Wilks, Chelsey; Rowan, Kael; Paradiso, Ann; Toledo, Arturo; McDuff, Daniel; Linehan, Marsha (CHI 2017, 2017)
A formative study of a mobile application for introducing skills related to Dialectical Behavior Therapy (DBT) is reviewed with an eye toward next iteration design. DBT is considered the gold standard for the treatment of suicide and borderline personality disorder, among other complex behavioral disorders. A multidisciplinary design team took licensed material from the creator of DBT, Marsha Linehan, and appropriated it for the mobile phone format and context of use. We walk through the design of the application including a conversational agent (“eMarsha”), videos of Dr. Linehan discussing therapeutic concepts and skills, and a module focusing on Mindfulness training. Initial evaluation of the app was encouraging with almost all users liking the flow and conversational user interface. In this paper, we focus on future work and the use of machine learning for precision psychology.